2021
DOI: 10.3389/fvets.2021.646458
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Stakeholders in the Design of One Health Surveillance Systems: A Participatory Approach

Abstract: Many One Health surveillance systems have proven difficult to enforce and sustain, mainly because of the difficulty of implementing and upholding collaborative efforts for surveillance activities across stakeholders with different values, cultures and interests. We hypothesize that only the early engagement of stakeholders in the development of a One Health surveillance system can create an environment conducive to the emergence of collaborative solutions that are acceptable, accepted and therefore implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Their participation to this study may increase the acceptability, the feasibility and the sustainability of the future community-based surveillance system. The participatory and One Health approach allowed the integration of actors from the different health sectors (human health, animal health, ecosystem health) that need to be involved in the surveillance of zoonotic diseases such VHFs [ 51 ]. The inclusion of the ecosystem health sector in disease surveillance systems is relatively new and we identified potential actors and communication channels [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their participation to this study may increase the acceptability, the feasibility and the sustainability of the future community-based surveillance system. The participatory and One Health approach allowed the integration of actors from the different health sectors (human health, animal health, ecosystem health) that need to be involved in the surveillance of zoonotic diseases such VHFs [ 51 ]. The inclusion of the ecosystem health sector in disease surveillance systems is relatively new and we identified potential actors and communication channels [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results highlighted the fact that community actors face different constraints and communicate with various stakeholders. This situation may delay the report of a suspected case to the relevant institutions and therefore the confirmatory diagnosis and outbreak control actions [ 51 , 61 ]. Our study showed interesting communication channels opportunities in the current health information exchange network to bypass potential barriers to health report.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed a semi-quantitative method based on the analysis of 13 criteria to assess the OH framework implementation in collaborative initiatives rapidly, whereas some participatory methods were developed to implement OH initiatives, such as disease surveillance, requiring several workshops and more time ( 74 ). If our approach delivers on results quickly, an action plan tailored to each initiative should be defined to improve its efficiency and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is being increasingly implemented to improve the impact of collaborative projects through easier, more efficient, and more fruitful collaborations. It has also been applied to strengthen stakeholders engagement and cooperation in surveillance systems to better tackle major challenges in public health such as antimicrobial resistance ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…One example of bringing the voice of different stakeholders to these discussions comes from our companion study on North American public attitudes regarding the issue of surplus calves (and cow calf separation) using an on-line survey (Ritter et al, 2022). In addition, a participatory approach was recently shown by Bordier et al (2021) to be an effective way to engage diverse stakeholders when designing a One health surveillance system to tackle antimicrobial resistance in Vietnam. A similar approach was used in the Netherlands for their pork opportunities project that set out to redesign a more sustainable pig husbandry system (Bremmer and Bos, 2017).…”
Section: Introductionmentioning
confidence: 99%